Delphi бағдарламалау ортасында сөзжұмбақ құрастыру - Нурмагамбетова, А.Ж. (My University, 2013)
Using the basic components of an object – Delphi 7 program adapted to draft a crossword puzzle, which can be used on non-traditional classes, intellectual games.